Prey Selection by Larval Micromus tas'lnQ,niae Walker (Neuroptera: Hemerobiidae) - Hussein, Mohd Yusof (1985)
The brown lacewing, Micromus tasmaniae, is the most common predator of potato aphids in South Australia. The probability of capture and prey preference of larval M. tasmaniae were measured for each instar of Myzus persicae Sulzer (the green peach aphid) at constant 15°e, 20° and 25°e. The probabiUty of capture of M. persicae by larval M. tasmaniae increased after each moult and declined just before moulting, especially at 15°e. Except for very small and young larvae, the predator larvae were able to capture efficiently both small and large prey. Young larval predators showed some preference for smaller prey~ whereas older larvae exhibited little or no preference. The effectiveness of M. tasmaniae larvae may vary considerably between seasons and climates.